Girls and women of color in STEM : their journeys in higher education - Abdelrahman, Nahed; Irby, Beverly J.; Ballenger, Julia, 1949-; Polnick, Barbara (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"The 11 chapters in this book provide a glimpse into the journeys that women from diverse backgrounds and ethnic differences take in their higher education undergraduate or graduate careers. The diverse women include ethnicities of Arabic, Asian, African-American, American Indian, and Latina"-- Provided by publisher.
Keywords: Minorities -- Education (Higher) -- United States -- Case studies.; Women -- Education (Higher) -- United States -- Case studies.; Science -- Study and teaching (Higher) -- United States -- Case studies.; Technology -- Study and teaching (Higher) -- United States -- Case studies.; Engineering -- Study and teaching (Higher) -- United States -- Case studies.; Mathematics -- Study and teaching (Higher) -- United States -- Case studies.; elektronické knihy; Case studies.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; electronic books